Optimization of Railway Line Maintenance in West Sumatra: A Literatur Review - Dasa Aprisandi (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
This study aims to analyze the maintenance strategy of railway lines in West Sumatra using the Life Cycle Cost (LCC) approach to determine the most economically efficient and sustainable maintenance option. The main issues raised are the high cost of reactive maintenance and the risk of operational disruption due to track damage. The research method involved collecting construction, operational, and maintenance cost data from railway operators, as well as LCC-based scenario simulations to compare preventive and reactive maintenance strategies. The results of the analysis show that the preventive maintenance strategy results in lower total life cycle costs, compared to the reactive strategy. In addition, the preventive strategy also supports operational sustainability by minimizing the risk of service disruption and improving user safety. SWOT analysis shows that LCC implementation has great potential to improve budget efficiency and support local economic growth, although challenges such as data limitations and natural disaster risks need to be mitigated. This research concludes that an LCC-based approach can be the basis for designing more effective, efficient and sustainable railway maintenance policies. Recommendations include prioritizing preventive maintenance, using monitoring technology, and strengthening supporting policies.